Physical Activity Opportunities for Older People - Ng, Yoke Leng (Curtin University, 2022)
Engaging in physical activity is important to optimise health and physical function. The findings in this thesis have contributed to validating a new assessment tool of physical performance (i.e., CBMS-Home) in higher functioning older adults for home or work settings, demonstrated the feasibility, safety and effects of a novel outdoor exercise park intervention for older adults with mild balance dysfunction, and described how older adults remained physically active during the coronavirus pandemic.